Pengaruh Latar Belakang Pendidikan dan Seleksi Terhadap Kompetensi dan Kinerja di Moderasi Pengawasan Pada Program BSPS Provinsi Riau - Bambang Priatama (Akuntansi & Ekonomika, 2020)
The study was conducted at the Ministry of Public Works and Public Housing Snvt Provision of Housing in Riau Province. The aim is to find out the direct effect of educational background and selection, on the competence and performance of field workers with supervision as a moderating variable. This study took a sample of 128 people. The variables used are educational background, selection, competence and performance and supervision. Data were analyzed using multiple linear regression analysis methods operated through the SPSS program. The results showed that there was an influence of educational background and selection on the competence of field workers. And simultaneously there is an influence of educational background and selection on competence. And there is an effect of competence on performance which is moderated by supervision. The better the supervision, the competence of field staff will increase.